2012
DOI: 10.1111/j.1365-3156.2012.03082.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting continued use of ceramic water purifiers distributed to tsunami‐affected communities in Sri Lanka

Abstract: Abstractobjectives There is little information about continued use of point-of-use technologies after disaster relief efforts. After the 2004 tsunami, the Red Cross distributed ceramic water filters in Sri Lanka. This study determined factors associated with filter disuse and evaluate the quality of household drinking water.methods A cross-sectional survey of water sources and treatment, filter use and household characteristics was administered by in-person oral interview, and household water quality was teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Water treatment and sanitation studies relied more heavily on self‐report to determine behaviour practice or technology presence. Three water treatment studies utilised spot checks to check levels of free chlorine residual , while four measured levels of microbial contamination . One study performed quick observations to determine how many SODIS (solar disinfection) bottles they could find on a roof at the time of survey .…”
Section: Resultsmentioning
confidence: 99%
“…Water treatment and sanitation studies relied more heavily on self‐report to determine behaviour practice or technology presence. Three water treatment studies utilised spot checks to check levels of free chlorine residual , while four measured levels of microbial contamination . One study performed quick observations to determine how many SODIS (solar disinfection) bottles they could find on a roof at the time of survey .…”
Section: Resultsmentioning
confidence: 99%
“…To model this effect, all simulated households are 2.05 times as likely to treat their water if their W Q i is above a varied threshold value (0 - 2000 CFU/100ml) (Casanova et al, 2012). Since this scenario is highly dependent on baseline filter compliance, the two parameters were varied concurrently for this experiment.…”
Section: Methodsmentioning
confidence: 99%
“…They also found that the odds ratio for using a filter was 1.7 when study participants were collecting surface water compared to 0.56 when using ground water which is of presumably better quality. A second study by Casanova et al (2012) found that study participants were almost twice as likely to use their CWF when E. coli were present in the water. They likewise found that those with tap water were less likely to use the filters compared to those who used well water exclusively.…”
Section: Introductionmentioning
confidence: 98%
“…To model this e↵ect, all simulated households are 2.05 times as likely to treat their water if it is above a given threshold value (Casanova et al , 2012). Since this scenario is highly dependent on baseline filter usage, the two parameters were varied concurrently for this experiment.…”
Section: Chapter 4 Sustainability Of Ceramic Filter Intervention 77mentioning
confidence: 99%
“…They also found that the odds ratio for using a filter was 1.7 when study participants were collecting surface water compared to 0.56 when using ground water which is of presumably better quality. A second study by Casanova et al (2012) found that study participants were almost twice as likely to use their ceramic water filter when there was E. coli present in the water. They likewise found that those with tap water were less likely to use the filters compared to those who used well water exclusively.…”
Section: Introductionmentioning
confidence: 99%